Traditional Mongolian Medicine Qiqirigan-8 alleviates non-alcoholic fatty liver disease via restoring gut microbiota and metabolism - Yang, Dandan; Wuyunsiqin,; YanNiu,; Hashentuya,; Tana,; Anna,; Ma, Mingxing; Zhao, Wenhui; Menggenduxi,; Wang, Minjie (Frontiers in Microbiology, 2025)
BackgroundMongolian Medicine Qiqirigan-8 (MMQ-8) is a traditional Mongolian medicine formula used to treat fatty liver disease. However, the material basis and in vivo metabolic process of the therapeutic effect of MMQ-8 on non-alcoholic fatty liver disease (NAFLD) remain unclear.MethodsThe chemical composition of MMQ-8 was determined using Ultra-high-performance liquid chromatography-quadrupole Exactive Mass spectrometry analysis (UHPLC-QE-MS). C57BL/6J mice were fed a choline-deficient diet for 12 weeks to induce a NAFLD model. Hematoxylin and Eosin (H&E)-staining, combined with serum biochemical indexes, was used to observe liver appearance and characterize the pathological changes and functions of the liver. HE staining and Alcian Blue-Phosphoric Acid Schiff (AB-PAS) staining of the colon, along with ZO-1 immunofluorescence expression in the colon were used to reveal the effect of MMQ-8 on the disruption of the intestinal epithelial mucosal barrier in the NAFLD. The expression of intestinal tight junction genes was analyzed by qRT-PCR to observe the protective effect of MMQ-8 against intestinal epithelial mucosal barrier disruption. Fecal metagenomics and serum non-targeted metabolomics were used to reveal the effects of MMQ-8 on the gut microbiota and metabolism in mice with NAFLD. Finally, we emphasize the interaction between gut microbiota and metabolites through Spearman correlation coefficient analysis.ResultsMongolian Medicine Qiqirigan-8 contains 17 active ingredients, which can reduce hepatic steatosis and lobular inflammation in mice with NAFLD, and have protective effects against liver injury. MMQ-8 reduced the infiltration of inflammatory cells in the colon epithelium of model mice while restoring the number of goblet cells. MMQ-8 significantly enhanced ZO-1 protein expression in the colon, as well as the mRNA expression of both ZO-1 and Occludin. Fecal metagenomics results showed that MMQ-8 reduced the Bacillota/Bacteroidota ratio in NAFLD mice. Increased the abundance of beneficial bacteria such as Porphyromonadaceae, Prevotella, and Bacteroidota. and suppressed the abundance of dysfunctional bacteria, such as Bacillota, Acetatifactor, and Erysipelotrichaceae. Furthermore, metabolomics studies revealed that MMQ-8 intervention significantly regulated the expression of metabolites related to glutathione metabolism, butyric acid metabolism, sphingolipid metabolism, and glycerophospholipid metabolism in NAFLD mice compared to the model group. These metabolic pathways play key roles in NAFLD. According to Spearman’s correlation coefficient analysis, up-regulation of Porphyromonadaceae, Prevotella, and Bacteroidota after MMQ-8 intervention was negatively correlated with LPC levels in glycerophospholipid metabolic pathways, while positively correlated with PC levels. In contrast, the relationship between Bacillota and Acetatifactor, which were down-regulated after MMQ-8 intervention, was the opposite. In addition, the up-regulation of Porphyromonadaceae, Prevotella, and Bacteroidota after MMQ-8 intervention was positively correlated with fumaric acid, 2-oxoglutaric acid, adenosine, and L-glutathione levels, while those down-regulated after MMQ-8 intervention were positively correlated with the levels of Bacillota, Acetatifactor were negatively correlated with all the above metabolites. Thus, glutathione metabolism, butyric acid metabolism, sphingolipid metabolism, glycerophospholipid metabolism and gut microbial ecosystem are tightly intertwined in this process.ConclusionIn summary, these findings indicate that MMQ-8 has a synergistic anti-NAFLD effect through its multi-component, multi-target, gut microbiota-modulating and multi metabolic pathway characteristics. The host’s regulation of specific gut microbiota and involvement in multiple metabolic pathways may be one of the important mechanisms by which MMQ-8 exerts its therapeutic effects on NAFLD. It is worth noting that metabolic pathways such as glutathione metabolism, butyric acid metabolism, sphingolipid metabolism, glycerophospholipid metabolism, and the gut microbiota ecosystem are closely intertwined in this process.